Pyoverdine, a siderophore from Pseudomonas aeruginosa, translocates into C. elegans, removes iron, and activates a distinct host response. Issue 1 (31st December 2018) - Kang, Donghoon; Kirienko, Daniel R.; Webster, Phillip; Fisher, Alfred L.; Kirienko, Natalia V.
ABSTRACT: Pseudomonas aeruginosa, a re-emerging, opportunistic human pathogen, encodes a variety of virulence determinants. Pyoverdine, a siderophore produced by this bacterium, is essential for pathogenesis in mammalian infections. This observation is generally attributed to its roles in acquiring iron and/or regulating other virulence factors. Here we report that pyoverdine translocates into the host, where it binds and extracts iron. Pyoverdine-mediated iron extraction damages host mitochondria, disrupting their function and triggering mitochondrial turnover via autophagy. The host detects this damage via a conserved mitochondrial surveillance pathway mediated by the ESRE network. Our findings illuminate the pathogenic mechanisms of pyoverdine and highlight the importance of this bacterial product in host-pathogen interactions.